Multidimensional Sleep Health Problems Across Middle and Older Adulthood Predict Early Mortality - Lee, Soomi; Mu, Christina X; Wallace, Meredith L; Andel, Ross; Almeida, David M; Buxton, Orfeu M; Patel, Sanjay R (The journals of gerontology. Series A, Biological sciences and medical sciences, 2024)
BACKGROUND: Having multiple sleep problems is common in adulthood. Yet, most studies have assessed single sleep variables at one timepoint, potentially misinterpreting health consequences of co-occurring sleep problems that may change over time. We investigated the relationship between multidimensional sleep health across adulthood and mortality. METHODS: Participants from the Midlife in the United States Study reported sleep characteristics in 2004-2006 (MIDUS-2; M2) and in 2013-2014 (MIDUS-3; M3). We calculated a composite score of sleep health problems across 5 dimensions: Regularity, Satisfaction, Alertness, Efficiency, and Duration (higher = more problems). Two separate models for baseline sleep health (n = 5 140; median follow-up time = 15.3 years) and change in sleep health (n = 2 991; median follow-up time = 6.4 years) to mortality were conducted. Cox regression models controlled for sociodemographics and key health risk factors (body mass index, smoking, depressive symptoms, diabetes, and hypertension). RESULTS: On average, 88% of the sample reported having one or more sleep health problems at M2. Each additional sleep health problem at M2 was associated with 12% greater risk of all-cause mortality (hazard ratio [HR] = 1.12, 95% confidence interval [CI] = 1.04-1.21), but not heart disease-related mortality (HR = 1.14, 95% CI = 0.99-1.31). An increase in sleep health problems from M2 to M3 was associated with 27% greater risk of all-cause mortality (HR = 1.27, 95% CI = 1.005-1.59), and 153% greater risk of heart disease mortality (HR = 2.53, 95% CI = 1.37-4.68). CONCLUSIONS: More sleep health problems may increase the risk of early mortality. Sleep health in middle and older adulthood is a vital sign that can be assessed at medical checkups to identify those at greater risk.
Keywords: poruchy spánku a bdění; rizikové faktory; Aged; spánek; Sleep; Spojené státy americké; Humans; senioři; lidé; Sleep Wake Disorders; hypertenze; United States; Hypertension; Risk Factors